Effect of Structural Alignment on Performance of Selected Micro Finance Institutions in Meru County, Kenya - Gatwiri, Linet; Obuba, Robert (Research Collaboration Community (RCC), 2024)
One of the most significant challenges affecting the financial sector pertains to issues such as loan non-repayment, a weak legal framework, and ineffective strategies for lender recourse and bad debt recovery. This has particularly impacted microfinance institutions, leading to Non-Performing Loans (NPLs) that diminish profits through credit losses and direct write-offs for loans turning into bad debts, ultimately reducing the funds available for lending. These challenges have posed a serious threat to the stability and survival of some Microfinance institutions in Kenya. Recognizing this gap, the research delved into exploring the effect of structural alignment on the performance of selected microfinance institutions in Meru County Kenya. Employing a descriptive research design, the study targeted 530 individuals comprising of Senior Managers, Tellers/Field Officers, and Customers of the ten selected Microfinance institutions within Meru County. Using Cochran (1977) formula as adopted by Chaokromthong and Sintao (2021) the study came up with a sample size of 223 respondents who were selected randomly to participate in the survey. Primary data was collected using questionnaires, and the semi-structured instrument was pilot-tested by 20 staff from Key Microfinance. The questionnaires were delivered to the respondents' workplaces and subsequently collected for analysis, which involved both descriptive and inferential statistical methods. The study's findings were presented through tables, figures, and qualitative discussions for analysis.